N-containing compounds from Hymenocallis littoralis and their cytotoxicity against Hep3B cells. (April 2022) - Pang, Xu; Duan, Zhi-Wen; Liu, Cai-Yan; Yu, Hai-Yang; Han, Li-Feng; Ma, Bai-Ping
Graphical abstract: Highlights: Two new alkaloidal flavonoids were isolated from H. littoralis . Glycosidic narciclasine derivative was obtained from H. littoralis for the first time. The chemical composition of H. littoralis was further understand. Abstract: A chemical study focusing on the N-containing constituents of Hymenocallis littoralis was carried out, leading to the isolation of two new alkaloidal flavonoids (1 –2 ) and five known alkaloids (3 -7 ). Structures of the isolated compounds were established mainly by spectroscopic techniques, including NMR spectroscopy and mass spectrometry as well as the CD experiment. These compounds were subjected to the in vitro cytotoxicity assays using Hep3B cells, and among them only the known pancratistatine (3 ) and lycorine (5 ) could significantly inhibit the Hep3B cell proliferation.